The impacts of tidal energy development and sea-level rise in the Gulf of Maine. (15th November 2019) - Kresning, Boma; Hashemi, M. Reza; Neill, Simon P.; Green, J. A. Mattias; Xue, Huijie
Abstract: In this study, we employed a 3-D and two-way nested Regional Ocean Modeling System (ROMS) to address several important outstanding issues regarding tidal energy development in the Gulf of Maine. We investigated the impact of projected sea-level rise (SLR) on the energy resources of the region, and examined how tidal dynamics will be influenced by energy extraction and/or SLR. Further, we assessed whether the effect of SLR on the generation of tides in the ocean (hence at the boundary of the region) is significant in these assessments. We find that the impact of SLR exceeds the impact due to energy extraction in the Gulf of Maine - even when considering very large energy extraction, of order 3.0 GW, in the Minas Passage. Although results showed that energy extraction does not significantly increase the amplitude of the tides in the far-field, a drastic change in the Bay of Fundy (e.g. full blockage) can lead to considerably higher amplitudes of tides (around 35 cm, or 12%) in the western Gulf of Maine. As a result of 1 m SLR, the theoretical tidal energy resources in some areas, including the Bay of Fundy can increase noticeably while any significant change in extracted energy highly depends on the turbine technology.